Students’ Basic Psychological Needs in Blended Teacher Learning Groups During COVID-19 - De Vocht, Ann; Vrieling-Teunter, Emmy; Hebing, Rosanne; Sins, Patrick; Vermeulen, Marjan (Proceedings of the International Conference on Networked Learning, 2024)
Teacher Learning Groups (TLGs) are social configurations in which student teachers (henceforth: students) learn together with peers, teacher trainers and teachers through social interactions (Doppenberg et al., 2012). Due to the restrictions caused by the COVID-19 pandemic, blended education has developed quickly. Blended education combines contact learning with distance learning ((Müller & Mildenberger, 2021). This workshop aims to shed light on how blended meetings interfere with the fulfilment of students’ basic psychological needs in TLGs. We also want to find out how to facilitate TLGs to support students’ basic psychological needs in times when social distancing is necessary or when blended education is convenient (e.g., to enhance the accessibility of education).